Peran Fraksi Partai Kebangkitan Bangsa di DPRD Kabupaten Sumenep Periode 2009-2014 - Kusliyatun, Kusliyatun (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article focuses on the role of the National Awakening Party (PKB) in the local parliament. This research concludes that the role of PKB of DPRD in Sumenep is committed by the spirit of fighting poverty and encouraging the grass root people-based APBD. These spirits are appropriate with the principle of maslahah (benefit) and âdl (justice). In line with the above conclusion, it is expected to the readers to be able to do more researches on the role of the National Awakening Party (PKB) in the local parliament. So that the further research will be able to fight the poverty of the grass root people based on the will of Siyasah Jinayah. Keywords: Candidate, individual, regional election, Islamic political jurisprudence